(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This research is titled “Revitalizing the Concept of Al-Fauzu in Tafsir Al-Ibriz for Strengthening Spirituality in the Digital Era”. Human beings who seek victory in life often do not understand what kind of victory they aim to achieve. Is that victory merely a matter of portraying achievements on social media, or can it truly foster mental resilience in this digital age, as Allah has promised in His words contained in the Qur’an? This study discusses how we can live a life strengthened against His tests by applying the concept of Al-Fauzu as explained in Tafsir Al-Ibriz. The main research question examined is: How is the concept of Al-Fauzu interpreted in Tafsir Al-Ibriz? This research employs a library research method, in which the researcher explores and examines library materials primarily Tafsir Al-Ibriz as the main source along with scientific works and other relevant literature. The findings of this study conclude that strengthening spirituality and mental resilience in the digital era can be achieved by maintaining faith and piety toward Allah and His Messenger, avoiding shirk, practicing honesty, being steadfast, and treating all creatures with kindness.